Covid-19 and women’s mental health: a case of women in polygamous marriages in Johane Marange Apostolic Church in Zimbabwe - Tsara, Lindah; Mudimeli, Lufuluvhi Maria (Penerbit Universiti Kebangsaan Malaysia, 2024)
The government's COVID-19 measures, including a nationwide lockdown and social distancing, presented a challenge for Johane Marange Apostolic Church (JMAC) in their implementation. Unfortunately, the women in the church could not voice their concerns about the leadership's shortcomings in this area. This study utilizes Gender justice theory to investigate how JMAC's teachings on polygamous marriages impacted the mental health of women during the pandemic. Through purposive sampling, interviews, and secondary sources, it was discovered that women in polygamous marriages in JMAC struggled mentally during COVID-19 due to their roles as wives and their positions in the church. While the church allows polygamous marriages, the study suggests that women's decision-making power should be elevated, and men should take more responsibility as breadwinners. The study also recommends that the church's teachings should be more adaptable during future pandemics to improve the mental health and well-being of women. Ultimately, the study proposes that congregants should be free to choose. The implication of the study will be for a paradigm shift in the beliefs and practices of JMAC, which encourage polygamy and result in mental health challenges during pandemics like COVID-19.